Optimization of Local Resources in the Implementation of the Food Security Program in Simbang Village - Tamrin, Saddam Husain; Sajidin, Muhammad (ARISTO, 2026)
The purpose of this study was to determine how the implementation of the food security program in Simbang Village, Pamboang District, Majene Regency. The analysis used Soren Winter's theory by identifying several key variables that can influence the success of the implementation of a program, namely the policy formulation process, the organizational behavior of the implementing actors, the behavior of bureaucrats at the lower level (Street Level Bureaucrats) and the response of the target group. This study uses a qualitative-descriptive method, where data analysis involves collecting open data based on general questions and information analysis, as well as writing short notes during the study. The results of the study indicate that the implementation of the food security program in Simbang Village, which is sourced from village funds in 2024, has been carried out well. Of the four key variables that influence the success of the food security program implementation in Simbang Village, the third variable is related to the street-level bureaucracy which is dominant in determining the success of the implementation of the food security program. The conclusion of this study, the Simbang Village government provides freedom for food security program activities in Simbang Village in achieving the welfare of the local community.